2022
DOI: 10.1186/s13256-021-03191-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute worsening of native lung fibrosis after single lung transplantation for pulmonary fibrosis: two case reports

Abstract: Background In patients receiving single lung transplantation for idiopathic pulmonary fibrosis, worsening of fibrosis of the native lung is usually progressive over time, with no significant effects on gas exchange. Case presentation Here, we describe the cases of two Caucasian male recipients of single lung transplants for idiopathic pulmonary fibrosis, 65 and 62 years of age, who exhibited acute worsening of lung fibrosis after an episode of seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Post-SLTx recipients are reliant on graft lung function, and even when complications occur in the native lung, symptoms are often minimal, making acute exacerbations in the native lung easy to overlook. Goletto et al reported cases of acute exacerbation in the native lung following infection with CMV and SARS-CoV-2 in two SLTx for IPF [ 23 ]. Despite progressive fibrosis in the native lung, infection in the graft improved, and the recipients were discharged safely.…”
Section: Discussionmentioning
confidence: 99%
“…Post-SLTx recipients are reliant on graft lung function, and even when complications occur in the native lung, symptoms are often minimal, making acute exacerbations in the native lung easy to overlook. Goletto et al reported cases of acute exacerbation in the native lung following infection with CMV and SARS-CoV-2 in two SLTx for IPF [ 23 ]. Despite progressive fibrosis in the native lung, infection in the graft improved, and the recipients were discharged safely.…”
Section: Discussionmentioning
confidence: 99%